Pengaruh Relationship terhadap Gaya Kepemimpinan dalam Sebuah Perusahaan PT DISTRIBUSI SUKSES MANDIRI - Alif Dava Mahesa; Yusep Irsad Najib Setiawan; Istialdi Pratama Haris; April Laksana (Institut Nalanda, 2025)
This research aims to analyze the influence of interpersonal relationships (relationships) on leadership style in a company at PT DISTRIBUSI SUKSES MANDIRI. An effective leadership style is considered crucial in creating a productive and harmonious work environment, while good relationships between individuals within a company can influence the quality of leadership. This research uses a quantitative approach by interviewing the operational director at the company. Data was collected through interviews that measured interpersonal relationships, leadership style, and team performance. The results of the analysis show that good relationships between employees and superiors significantly influence the leadership style applied, with more inclusive and participative leadership appearing in companies with stronger interpersonal relationships. These findings indicate the importance of effective relationship management in improving leadership quality and organizational performance. This research provides practical implications for companies to strengthen interpersonal relationships in the workplace as a strategy for building more adaptive and collaborative leadership.